Owidiusz w międzygatunkowej rozterce – „Amores” II 18 - Miazek-Męczyńska, Monika (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2023)
Elegy 18 from Book II of Amores, presented in the article in a new translation into Polish, explains why Ovid decided to abandon epic poetry and tragedy in favour of elegiac poetry. Although the poet jokingly points to Cupid, Corinna and his own laziness as the reasons, in fact, he shows that this literary genre is extremely attractive to authors who, like himself, writing about love can refer not only to personal experiences, but also to threads traditionally reserved for epics or tragedy. As evidence, Ovid invokes his Heroides and invites his friend, the poet Pompey Macer, to follow him in elegiac poetry. By recalling the works of Macer and Sabinus, Amores II 18 is also proof of the importance of friendship between the writers of the Augustan era, whose works bear visible traces of mutual influences and interactions.